2016
DOI: 10.1007/s13277-016-5241-5
|View full text |Cite
|
Sign up to set email alerts
|

MiR-541-3p reverses cancer progression by directly targeting TGIF2 in non-small cell lung cancer

Abstract: Lung cancer remains a leading cause of cancer-associated mortality worldwide, and non-small lung cancer (NSCLC) is responsible for over 80 % of lung cancer-related deaths. Identifying novel molecular biomarker that can inhibit the progression of lung cancer will facilitate the development of new treatment strategies. Herein, we demonstrated that miR-541-3p is a tumor-suppressor microRNA (miRNA) in NSCLC progression. We found that expression of miR-541-3p was decreased obviously in NSCLC tissues and plasma. Dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 24 publications
6
25
0
Order By: Relevance
“…Another study revealed that miR-541 is involved in regulating vascular smooth muscle cell proliferation [19]. In the present study, our results indicating that miR-541 expression is decreased in SCLC are consistent with the findings by Lu [18]. In addition, the finding that miR-541 is a tumor suppressor in both breast cancer and SCLC makes miR-541 potentially valuable in the clinical treatment of human tumor diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Another study revealed that miR-541 is involved in regulating vascular smooth muscle cell proliferation [19]. In the present study, our results indicating that miR-541 expression is decreased in SCLC are consistent with the findings by Lu [18]. In addition, the finding that miR-541 is a tumor suppressor in both breast cancer and SCLC makes miR-541 potentially valuable in the clinical treatment of human tumor diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Since our study reports TGIF2 as a novel miR‐490‐3p target not reported so far in any cancer, thus we considered it for downstream functional analysis. Literature so far suggests the dual nature of TGIF2 where it may function as a tumor suppressor or as an oncogene . Also, in line with our observation, TGIF2 was shown to promote aggressive phenotype in gliomas .…”
Section: Discussionsupporting
confidence: 89%
“…Upregulation of eca‐miR‐493b and eca‐miR‐541 was associated with advanced tumour stage (ESA) in ES tumours and might therefore also be of prognostic significance. Interestingly, these miRNAs possess rather tumour‐suppressive functions in diverse human cancers where they are often downregulated . If upregulation of eca‐miR‐493b and eca‐miR‐541 drives oncogenesis in ES and whether inhibition of these two miRNAs could possibly stop ES disease progression, needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%